A framework based on fuzzy logic to manage risk in an open innovation context - Santos, Ricardo (2021)
Virtual enterprises (VE), is well-known to make use of open innovation to achieve competitiveness, through innovation on product development. However, its limited resources, combined with the innovation resulted from the diversity of partners involved, rises some challenges to its management, specifically regarded with risk management. To fulfill these requirements, risk management's models, have been conceived to assist managers, on preventing threats with such risks, although without adequately incorporate the influence of each process domain on product development, as well as the subjectivity regarding human perception. In order to consider these issues, this work presents an approach, supported by fuzzy logic, to assess the risk's level on product development in an open innovation context. The model robustness, will be assessed through a case study, where it will be also discussed the benefits and challenges found.